1998
DOI: 10.1097/00005650-199805000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Characteristics Associated With Women's Satisfaction With Prenatal Care

Abstract: Knowledge of the care characteristics that impact low-income pregnant women's satisfaction can be utilized to alter service delivery to increase use of prenatal care and ultimately to improve perinatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 25 publications
1
37
0
6
Order By: Relevance
“…A review on general health services delivery in China reported that many patients complained about unclear information about services they received and a few of them or their relatives had open conflict with health providers [27]. Studies in both industrialised and developing countries have found that good patient-provider interaction was associated with increased women's satisfaction [28,29], which was considered as one of the major factors influencing the use of prenatal care and the effect of care [30]. The lack of clear and effective communication suggested in this study may not only undermine the provider-user relationship, but also potentially affect health seeking behaviour if patients are unwilling to seek care due to lack of trust.…”
Section: Discussionmentioning
confidence: 99%
“…A review on general health services delivery in China reported that many patients complained about unclear information about services they received and a few of them or their relatives had open conflict with health providers [27]. Studies in both industrialised and developing countries have found that good patient-provider interaction was associated with increased women's satisfaction [28,29], which was considered as one of the major factors influencing the use of prenatal care and the effect of care [30]. The lack of clear and effective communication suggested in this study may not only undermine the provider-user relationship, but also potentially affect health seeking behaviour if patients are unwilling to seek care due to lack of trust.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we analyzed the differences between the perspectives of women in the intervention and control clinics, focusing only on those specific aspects that changed as a result of the introduction of the new ANC model (number and spacing of visits, information provided, etc.) Our study did not explore women's satisfaction with any other aspects of ANC such as technical quality, physical environment, access and continuity of the provider [37,38] that were not modified with the intervention, or the differences in users' satisfaction associated with ANC received in different types of facilities (i.e. private or public.)…”
Section: Discussionmentioning
confidence: 99%
“…The client satisfaction survey was an adaptation of a client satisfaction survey used in the United States for prenatal clinic visits (Handler, Rosenberg, Raube, & Kelley, 1998). Again, we consulted with Malawian clinical experts to determine appropriateness of the items for health workers in Malawi.…”
Section: Methodsmentioning
confidence: 99%